Epigenetic control of region‐specific transcriptional programs in mouse cerebellar and cortical astrocytes. Issue 9 (24th May 2021) - Welle, Anna; Kasakow, Carmen V.; Jungmann, Annemarie M.; Gobbo, Davide; Stopper, Laura; Nordström, Karl; Salhab, Abdulrahman; Gasparoni, Gilles; Scheller, Anja; Kirchhoff, Frank; Walter, Jörn
Abstract: Astrocytes from the cerebral cortex (CTX) and cerebellum (CB) share basic molecular programs, but also form distinct spatial and functional subtypes. The regulatory epigenetic layers controlling such regional diversity have not been comprehensively investigated so far. Here, we present an integrated epigenome analysis of methylomes, open chromatin, and transcriptomes of astroglia populations isolated from the cortex or cerebellum of young adult mice. Besides a basic overall similarity in their epigenomic programs, cortical astrocytes and cerebellar astrocytes exhibit substantial differences in their overall open chromatin structure and in gene‐specific DNA methylation. Regional epigenetic differences are linked to differences in transcriptional programs encompassing genes of region‐specific transcription factor networks centered around Lhx2/Foxg1 in CTX astrocytes and the Zic/Irx families in CB astrocytes. The distinct epigenetic signatures around these transcription factor networks point to a complex interconnected and combinatorial regulation of region‐specific transcriptomes. These findings suggest that key transcription factors, previously linked to temporal, regional, and spatial control of neurogenesis, also form combinatorial networks important for astrocytes. Our study provides a valuable resource for the molecular basis of regional astrocyte identity and physiology. Main Points: The epigenomes of cortical and cerebellar astrocytes are highly distinct. We find an epigenetically primed network around the transcription factors Lhx2 and Foxg1 in cortical astrocytes, while Zic1/Zic4 form a network in cerebellar astrocytes.